Local Wisdom-Based Skills Apprenticeship Process for Women Ex-Migrant Workers in Kediren Village, Magetan District, Indonesia - Purwito, Lasi; Rasyad, Ach.; ., Zulkarnain; Raharjo, Kukuh Miroso (Journal of Ecohumanism, 2024)
Kediren Village is a village where most women of productive age from the village are former migrant workers who have minimal skills and knowledge when returning to their hometown. The skills apprenticeship process organized by the Head of Kediren Village aims to reduce the population's poverty rate and unemployment for former migrant workers. Skills apprenticeships organized based on local wisdom can positively impact women who are former migrant workers, including providing additional activities that can be carried out to earn additional income. This research examines the importance of skills apprenticeships for female former migrant workers in Kediren Village. This research uses a qualitative approach with a case study method. The location of this research is Kediren Village, Lembeyan District, Magetan Regency, East Java. The informant criteria included the Kediren village head, chief, female former migrant workers, stakeholders, and community leaders as data sources in the research. Data was collected using in-depth interview techniques, observation, and documentation studies. Data analysis was carried out using the Miles and Huberman interactive model. This research shows that the skills apprenticeship process aimed at female ex-migrant workers can positively impact their ability to make traditional batik to support progress in improving the village economy and for individuals, as well as actively participating in activities organized by the chief executive. Research suggestions are aimed at female former migrant workers to develop the learning they have obtained in their daily activities and as an ongoing entrepreneurial field.